2013
DOI: 10.1016/j.tcb.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of cell death pathways: insight from the fly ovary

Abstract: Multiple types of cell death exist including necrosis, apoptosis, and autophagic cell death. The Drosophila ovary provides a valuable model to study the diversity of cell death modalities, and we review recent progress to elucidate these pathways. At least five distinct types of cell death occur in the ovary, and we focus on two that have been studied extensively. Cell death of mid-stage egg chambers uses a novel caspase-dependent pathway that involves autophagy, and triggers phagocytosis by surrounding somati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(102 citation statements)
references
References 87 publications
1
88
0
12
Order By: Relevance
“…5B, arrow), indicative of failures in membrane integrity (Nishimura and Lemasters, 2001;Carter et al, 1994). It is known that germ cells in both the ovary (Jenkins et al, 2013) and testis (Yacobi-Sharon et al, 2013) can undergo necrosis, which involves loss of plasma membrane integrity (McCall, 2010). Taken together, these data show that depletion of Chic leads to failure of the somatic permeability barrier.…”
Section: Chic Is Required In the Soma For Fertilitymentioning
confidence: 62%
“…5B, arrow), indicative of failures in membrane integrity (Nishimura and Lemasters, 2001;Carter et al, 1994). It is known that germ cells in both the ovary (Jenkins et al, 2013) and testis (Yacobi-Sharon et al, 2013) can undergo necrosis, which involves loss of plasma membrane integrity (McCall, 2010). Taken together, these data show that depletion of Chic leads to failure of the somatic permeability barrier.…”
Section: Chic Is Required In the Soma For Fertilitymentioning
confidence: 62%
“…The procedures of apoptosis are formed as follows: Receiving apoptotic signals leads to cytomorphological alterations, the interaction between the intermolecular apoptotic proteins, activation of the caspase enzyme that acts upon cytoskeleton proteins, mitochondria, nuclear membrane or chromatin to cleave proteins and substrates, causing the DNA to fragment, releasing the cytoplasm enclosed by the plasma membrane, eventually leading to cell death (10)(11)(12)(13)(14). Currently, it is known that the extrinsic or death receptor pathway, the intrinsic or mitochondrial pathway and the perforin/granzyme pathway are the major apoptotic pathways to activate caspases (12,(15)(16)(17).…”
Section: Inducing Cellular Apoptosismentioning
confidence: 99%
“…Moreover, in D. melanogaster seven, caspases homologous to mammalian enzymes have been identified: three initiators (Dredd, Dronc and Strica) and four effectors (Drice, Dcp-1, Decay and Damm) (Cooper et al 2009). This suggests that, at least in part, vertebrate/mammalian apoptosis proteins may be conserved (Denton et al 2013;Jenkins et al 2013). On the other hand, it was found that, similar to in mammals, Bcl-2 proteins and mitochondrial remodeling contribute to cell death in Drosophila, but their mechanisms may differ.…”
mentioning
confidence: 99%
“…In Drosophila mid-stage death in the ovary, mitochondria remodel into clusters, which are engulfed and then degraded by somatic follicle cells. This is dependent on the Bcl-2 genes Debcl and Buffy, mitochondrial remodeling genes, caspases, and autophagy genes (Jenkins et al 2013).…”
mentioning
confidence: 99%